Research data sharing practices of academics in Nigeria: The effects of organizational culture / Khalid Ayuba Abdullahi - Khalid Ayuba, Abdullahi (2019)
Research data sharing was perceived differently among academics worldwide. Even though general view of data sharing is essential in enabling academics to have ease in conducting research, but effort, time and energy involved in data sharing practices made it difficult to some researchers particularly in periphery countries such as in Nigeria landscape. Therefore, this study was conducted with the following purposes: i) to examine how does Nigerian academic community perceive data sharing, ii) to investigate factors that influence academics’ data sharing practices and to see the differences of data sharing between sciences and social sciences scholars. This study was conducted based on the theory of organizational culture in viewing the way academics share their research data in the lens of collective values, beliefs and principles of organizational members. Quantitative research approach was used for collecting data by means of semi structured interview and survey questionnaires. Data was gathered from academics in 5 Nigerian universities. A total of 22 academics were interviewed to investigate their perception, motivation and perceived risk of research data sharing. The interview was analyzed using thematic analysis technique. The finding from the interview revealed discipline receptive, funding agencies, and journal publishers as some of the ways academics become aware of data sharing practices and academics understood research data sharing differently with majority seen it as a progress to research while few on the opinion that is of no use. Cloud source repository and personal websites are identified to be some of the data sharing practices’ platforms. Expecting more citations, academic promotion, recognition, monetary incentives are acknowledged to be some of the motivational factors for data sharing practices. Furthermore, data privacy and cultural orientations are realized to be some of the risks involved in data sharing practices. The findings from the interviews were used in the development of the survey instrument to suit more appropriately Nigerian context which is to investigate factors that could influence academics in Nigeria on research data sharing. The survey questionnaires were disseminated randomly to 378 academics in Nigeria using stratified sampling technique. Responses from the survey questionnaire were analysed using the Structural Equation Model (SEM) SmartPLS software. The survey findings indicated three categories of factors namely, i. personal attributes that comprised effort expectancy, legitimate concern, beneficence, conditions for data sharing and expected rewards, ii. Organizational attributes that involved research funders, perceived pressure by journal, data repository, organizational structure, infrastructure and policy and guidelines, iii. Social attributes that consist of community culture and discipline norms influence data sharing practices among Nigerian academics. This study hypothesized 13 relationships and the path coefficient analysis shown all hypotheses supported considering a p. value <0.05. The discussion on influence of academics’ data sharing practices revealed nine variables had a significant positive coefficient (expected rewards (β=0.235, p<0.05), beneficence (=β 0.157, P<0.05), discipline norms (β = 0.169, P<0.05), data repository (β = 0.082, P<0.05), research funders (β = 0.034, P<0.05), infrastructure (β = 0.039, P<0.05), perceived pressure by journal (β =0.096, P<0.05), organizational structure (β =0.094, P<0.05) and policy/guidelines (β = 0.049, P<0.05). with four having negative significant coefficient (conditions for data sharing (β = -0.098, P<0.05), legitimate concern (β =-0.130, P<0.05), community culture (β =-0.096, P<0.05) and effort expectancy (β =-0.110, P,0.05). The data analysis demonstrated differences between sciences and social sciences academics in their data sharing practices in which academics from the sciences were more willing to share their research data as compared to academics in social sciences counterparts. The findings of this study is important to provide more understanding on the research data sharing practices particularly among academics in Nigeria where the community culture and ICT infrastructure is different from other part of the world. Three contributions are highlighted comprising body of knowledge by addressing issues related to awareness, understanding, familiarity, motivations and risks involved in data sharing among academics. Theoretically by assisting in discovering new items such as community culture and infrastructure and practice by encouraging the participation of academic towards data sharing practices particularly in Nigeria and or the worldwide.